THE LEGAL POSITION OF THE HUMAN RESOURCES POSITION IN REPRESENTING THE LEGAL INTERESTS OF EMPLOYERS IN THE WORK AGREEMENT BETWEEN EMPLOYERS AND EMPLOYEES - Wicaksono, Luther Pamungkas; Prasetyo, Dr. Dossy Iskandar (jfpublisher, 2024)
Human resources positions in companies hold a strategic role in empowering and optimizing employee performance, which contributes to the company’s progress. As an employee of the company, the human resources position holds a legal position in managing employee matters and board of directors policies that represent the company’s interests. In order to carry out this role, the human resources position requires authorization in order to ensure a strong legal foundation, thus ensuring that the actions taken are not detrimental to the company. This research applies normative juridical method with secondary data collected through literature study and analyzed qualitatively normative. HR’s position is important in representing the employer’s legal interests, but is limited by company regulations. Delegation of legal authority must be regulated by law and cannot be arbitrary. Rights and obligations in the employment agreement remain with the employer unless there is an official power of attorney. Without a power of attorney, HR actions are invalid. Proper delegation provides a strong legal basis for HR, especially in employment agreements. Employment Law emphasizes the importance of official delegation for HR actions to be valid, so without a power of attorney, legal responsibility becomes personal, not corporate.